(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Saffron tincture is widely used in folk medicine. The pharmacological feature of the saffron plant is that it has a wide range of effects, eliminates obstruction and resistance in the layer of blood vessels and kidney tubules, reduces the process of blood fibrinolysis, and the release of histamine into smooth muscles. It eliminates their spasm by blocking secretion and reduces the need for broncholytic drugs due to its less bromolytic effect.